Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Elsa Adps Di Bandar Udara Hang Nadim Batam - Mesri Silalahi (Universitas Putera Batam, 2014)
ELSA ADPS used by Hang Nadim Airport Batam has been used since 2012, this system is used to manage the news flying as flight plan, departure, landing, and flight meteorological news which will then be sent to each units and airports require. This study also aimed to determine the effect on the performance aspects of human resources information systems, to determine the effect of involvement and support from managers on the performance of information systems, to determine the effect of system compatible with other systems on the performance of information systems, to determine the effect of user involvement on system performance information, to determine the effect of simultaneous aspects of human resources, involvement and support from managers, system compatible with other systems, the existence of the issue of user involvement and user behavior on system performance ELSA ADPS. Data retrieval techniques with distributing questionnaires to all employees of Hang Nadim Airport Batam in particular the use of information systems while the ELSA ADPS data processing using statistical program SPSS to analyze the data using descriptive, test the data quality, hypothesis testing, simultaneous test (F) and partial test (T). The findings in this research that there is positive between the HR aspects of the performance ELSA ADPS, there is a positive effect between involvement and support of the manager of the Performance Information Systems ELSA ADPS, there system compatible with other systems on the performance of ELSA ADPS, there is no the existence of the influence of user involvement and the issue of user behavior on system performance ELSA ADPS. Aspects of human resources, involvement and support from managers, system compatible with other systems, the existence of user involvement and user behavior issues jointly affect the system performance ELSA ADPS.